Uji Organoleptik Serbuk Daun Sungkai (Albertisia Papuana Becc.) Sebagai Penyedap Rasa Alami - Asro L Indrayanti; Dewi R Juwita; Marni Marni; Arief R Hakim (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2019)
The tendency for excessive consumption of MSG has prompted various studies to find a replacement. One of the ingredients studied is Sungkai leaf powder (Albertisia papuana Becc) which has been used by people in Kalimantan as a flavor enhancer. This study aims to determine the dosage of use of sungkai leaves which is preferred by panelists through organoleptic tests. Panelists (as many as 104 panelists) were selected by incidental sampling from among housewives (32), food traders (17), students of the UPR industrial technology program (41) and ordinary people (14). The treatments were made in 5 levels, namely control (M1), 0.5 gram / L (M2), 1.0 gram / L (M3), 1.5 gram / L (M4) and 2.0 gram / L (M5) ). The results showed that Sungkai leaf powder (Albertisia papuana Becc) can be used as a natural food delicacy because it can raised umami (delicious taste), which is caused by the synergy of protein, natrium and free amino acids. The panelists' response to the optimal dose of using sungkai leaf powder varies greatly depending on the habits and tastes of the panelists. This study also concluded that the application of Sungkai leaf powder was not too dominant in adding flavor and changing the color of the dishes.